2012
DOI: 10.1097/wno.0b013e318240204d
|View full text |Cite
|
Sign up to set email alerts
|

Visual Pathway Axonal Loss in Benign Multiple Sclerosis

Abstract: Background Benign MS, traditionally defined as EDSS ≤3 and ≥15 years’ disease duration, is thought to follow a milder course. We determined the extent of visual pathway axonal loss by optical coherence tomography (OCT) retinal nerve fiber layer (RNFL) thickness in a benign MS cohort, and examined the relation to vision and quality of life (QOL). Methods In this longitudinal study of vision in MS at three academic centers, a subset of patients with EDSS, visual function, OCT, and QOL assessments was analyzed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 43 publications
3
30
0
Order By: Relevance
“…Galetta et al and Sakai et al reported no difference in RNFL thickness between BMS and typical MS. The authors even suggested consistent trends of greater worsening for benign patients [38,61]. A more recent study, however, including all retinal layers stated that the macular GCC and the peripapillary RNFL and inner nuclear layer (INL) showed significantly more thinning in typical MS, compared with BMS.…”
Section: • • Retinal Layer Thicknesses and Disease Typementioning
confidence: 94%
“…Galetta et al and Sakai et al reported no difference in RNFL thickness between BMS and typical MS. The authors even suggested consistent trends of greater worsening for benign patients [38,61]. A more recent study, however, including all retinal layers stated that the macular GCC and the peripapillary RNFL and inner nuclear layer (INL) showed significantly more thinning in typical MS, compared with BMS.…”
Section: • • Retinal Layer Thicknesses and Disease Typementioning
confidence: 94%
“…Designed for the assessment of ophthalmologic diseases (Mangione et al, 2001) the NEI-VFQ is a valid and reliable instrument which was frequently used in studies focusing on the impact of visual field defects on subjective vrQoL after central visual pathway lesions (Cole et al, 2000; Beck et al, 2004; Raphael et al, 2006; Papageorgiou et al, 2007; Gall et al, 2009, 2010; Wagenbreth et al, 2011; Galetta et al, 2012; Walter et al, 2012; Jasse et al, 2013). It was demonstrated that diminished vrQoL was significantly related to the size of the visual field defect (e.g., Gall et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that patients with ''benign MS'' have similar and perhaps even greater degrees of visual pathway involvement. 56 To evaluate the retinal neurodegeneration in patients with MS, measurement of the retinal nerve fiber layer (RNFL) thickness using optical coherence tomography (OCT) has been proposed as a potential biomarker of axonal damage in MS. A cross-sectional, case-control study of 39 patients with MS circumpapillary RNFL thickness in affected eyes was decreased compared with nonaffected eyes. The thickness of the macular ganglion cell complex (GCC) had the highest sensitivity and specificity in detecting axonal loss independent of ON.…”
Section: Optic Neuritis and Multiple Sclerosismentioning
confidence: 99%